Clustering of lifestyle cardiovascular risk factors among healthy government servants in Kuala Terengganu: who and what to target - Nurulhuda, Mat Hassan; Norwati, Daud; Mazubir, N.N. (Penerbit Universiti Sultan Zainal Abidin, 2020)
Cardiovascular disease is the leading cause of death and disability among men and women in nearly all nations, including Malaysia. Lifestyle cardiovascular risk factors such as dietary habits, physical inactivity and smoking are considered fundamental risk factors for cardiovascular disease. Previous studies showed that the clustering of cardiovascular risk factors significantly increase the risk of developing cardiovascular events. Surveillance of these key modifiable risk factors, including its clustering and study of factors associated is needed to monitor the magnitude of the problem and effects of our interventions. This study aimed to determine the prevalence and factors associated with clustering of lifestyle cardiovascular risk factors among government servants in Kuala Terengganu, Malaysia. This was a cross-sectional study conducted between June and September 2013 among 121 government servants, selected using simple random sampling from all servants asymptomatic of cardiovascular disease at a multi-department government center in the capital of Terengganu. A questionnaire, which consisted of socio-demographic data, International Physical Activity Questionnaire (IPAQ) and the dietary component of WHO STEPs, were used as the research tools. Clustering of lifestyle cardiovascular risk was defined as the presence of two or more of the lifestyle risk factors. Prevalence of clustering of lifestyle risks in this study was 57% (95% CI: 0.47, 0.67). Respondents with income less than RM3, 000 was significantly associated with clustering of lifestyle cardiovascular risks (p=0.032, OR 2.57, CI: 1.08, 6.07). This study provides evidence of clustering of lifestyle risks in the local asymptomatic healthy subjects. Therefore, comprehensive lifestyle interventions may be an effective strategy for controlling CVD risk factors, especially among those with low socioeconomic status where affordable interventions should be suggested. A more effective approach should be identified to promote affordable healthier diet and healthy lifestyle activities.